2017
DOI: 10.1108/wjemsd-06-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Moderating relationship of institutions for opportunity entrepreneurship and economic development

Abstract: Purpose The purpose of this paper is to develop a conceptual framework that illustrates how resource-based countries, such as those in the Gulf Cooperation Council, can move their economies towards a more sustainable diversified model, through creating and fostering institutions that are conducive for opportunity entrepreneurship. Design/methodology/approach Several key variables pertaining to formal and informal institutions which impact opportunity entrepreneurship are presented in a conceptual framework b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 105 publications
(294 reference statements)
2
28
0
Order By: Relevance
“…The interpretation of the previous results could be explained in three ways. First, the previous results could suggest that entrepreneurs who are associated with higher risk levels tend to obtain financial resources from social networks and family connections; this may be because existing financial institutions are underdeveloped and less likely to support their new ventures (Ho and Wong, 2007;Chowdhury et al, 2015b;Fuentelsaz et al, 2015;Ghura et al, 2017). Second, another interpretation for the findings was suggested by Wennekers et al (2005), who argued that emerging economies have higher rates of necessity entrepreneurship (i.e., informal entrepreneurship), which does not require large amounts of credit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interpretation of the previous results could be explained in three ways. First, the previous results could suggest that entrepreneurs who are associated with higher risk levels tend to obtain financial resources from social networks and family connections; this may be because existing financial institutions are underdeveloped and less likely to support their new ventures (Ho and Wong, 2007;Chowdhury et al, 2015b;Fuentelsaz et al, 2015;Ghura et al, 2017). Second, another interpretation for the findings was suggested by Wennekers et al (2005), who argued that emerging economies have higher rates of necessity entrepreneurship (i.e., informal entrepreneurship), which does not require large amounts of credit.…”
Section: Resultsmentioning
confidence: 99%
“…Second, another interpretation for the findings was suggested by Wennekers et al (2005), who argued that emerging economies have higher rates of necessity entrepreneurship (i.e., informal entrepreneurship), which does not require large amounts of credit. Lastly, although this latter idea could be right, the results also suggested that entrepreneurs may later depend on alternative sources to fund their growing businesses, such as venture capital funds, angel investors and corporate investors, due to the lack of adequate financial infrastructure (Bowen and De Clercq, 2008;Aidis, 2012;Ghura et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This implies that the change of the institutional framework affects the entrepreneurial activity by influencing the business environment [2]- [4]. Therefore, as suggested in the literature [5], [6], certain interconnection of institutions and the business climate is envisaged. However, ways in which changes in institutional environment affect the business climate have not received sufficient attention from scholars [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is the place where entrepreneurs may intervene in an innovative way [18] and boost the link between entrepreneurship and innovation in order to generate better and more functional recycling solutions. Therefore, conceptual and empirical studies were run in order to better demonstrate how much entrepreneurship determines economic growth [19,20], concludes towards a circular economy [21], boosts innovation or vice-versa [22][23][24], and even show the link between these three concepts: innovation, entrepreneurship, and economic growth [25]. Moreover, empirical studies were run in order to find out innovative solutions for smart partnerships [26] and sustainable development [27].…”
Section: Introductionmentioning
confidence: 99%